686Evaluation of the impact of National Health Mission on maternal health outcomes. (2nd September 2021) - Sangwan, Garima; Lakshmi, P.V.M.; Goel, Aarti; Gupta, Madhu; Prinja, Shankar; Kumar, Rajesh
Abstract: Background: The National Health Mission (NHM) was launched in 2005 by the Government of India. As NHM has completed about 15 years (2005-2020), there is a need to review the impact of NHM on health measures. Methods: Logic model (input-process-output-outcome-impact) was used to measure the impact of National Health Mission on maternal health outcomes in India. We studied the impact of NHM by comparing the proportion of women who had first-trimester registration, institutional delivery, postnatal check-ups before NHM (NFHS- 3 data) and after NHM (NFHS-4 data) among those who had a delivery in the last five years preceding the date of the survey after adjusting for sociodemographic factors, road density, telephone density and health worker density. Results: The Health worker density increased from 32.67 to 50.29 per 10000 population in post NHM period as compared to pre NHM period. Beds per 10, 000 population increased from 4.43 in 2005 to 5.96 in 2015. There was a significant increase in the proportion of first-trimester registration from 57.3% to 67.4%, in institutional delivery rate from 41.6% to 87.7% and postnatal check-ups from 42.4% to 72.3% from the year, 2005 to 2015. The Maternal mortality ratio declined from 250 to 130 per lakh childbirths between 2005 and 2015. Conclusions: NHM has led to an improvement in maternal health-related outcomes in the country. Key messages: The learnings from NHM can be utilized to improve further the outcomes for achieving Universal Health Coverage (UHC) by 2030.